2016
DOI: 10.1002/jbm.b.33727
|View full text |Cite
|
Sign up to set email alerts
|

Sinus augmentation using a histone deacetylase inhibitor in a calcium sulfate carrier in rabbit: A pilot study

Abstract: Histone deacetylase inhibitors such as sodium butyrate (SB) have been suggested to be promising candidate small molecules for bone regeneration. In this study, the capacity of SB loaded onto calcium sulfate (CaS) to enhance bone formation was investigated in a rabbit sinus model. Following preparation of the sinus access window on a randomly selected side, SB loaded onto CaS (CaS/SB) was grafted in five rabbits, and CaS alone (control) was grafted in another five rabbits. The animals were euthanized after 4 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
(63 reference statements)
0
5
1
Order By: Relevance
“…The primary goal of this study was to determine the synergistic effects of SB and DMOG combined with CaS on vertical bone augmentation by using an onlay graft model in the rabbit calvarium. This study found that SB and DMOG appeared to exert minimal synergistic effects on new bone formation in vertical bone augmentation, which contrast with previous in vivo studies finding improved bone regeneration within contained defects (Cha et al, ; Liu, Wang, Wu, Ni, & Liang, ; Woo et al, ).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The primary goal of this study was to determine the synergistic effects of SB and DMOG combined with CaS on vertical bone augmentation by using an onlay graft model in the rabbit calvarium. This study found that SB and DMOG appeared to exert minimal synergistic effects on new bone formation in vertical bone augmentation, which contrast with previous in vivo studies finding improved bone regeneration within contained defects (Cha et al, ; Liu, Wang, Wu, Ni, & Liang, ; Woo et al, ).…”
Section: Discussioncontrasting
confidence: 99%
“…DMOG and SB were used at a concentration of 100 μmol/L in this study, which was based on previous studies (Cha et al, ; Jung et al, ; Woo et al, ). A previous in vitro study found that DMOG and SB enhanced the differentiation of MC4 cells and increased the expression of angiogenic and osteogenic factors (Woo et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The metabolic rate is three to four times faster in rabbits than in humans, and the effects on bone healing can be confirmed within weeks [ 25 ]. Several studies using this model have shown differences between control and experimental groups at healing periods of 2 and 4 weeks [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%